2015
DOI: 10.1007/s12070-015-0853-4
|View full text |Cite
|
Sign up to set email alerts
|

Voice Outcome Following Carbon Dioxide Laser Assisted Microlaryngeal Surgery

Abstract: Very few studies have been conducted in South Indian population to evaluate glottic function and voice outcome following carbon dioxide (CO 2 ) laser assisted microsurgery for benign lesions of the larynx. This is a descriptive study which aims at assessing the voice outcome (perceptual and acoustic) and vocal fold function (stroboscopic) following CO 2 laser excision in benign vocal fold lesions. 50 adult patients with benign laryngeal lesions were selected to undergo CO 2 laser excision in super-pulse mode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The improvement in the acoustic parameters can be explained on the basis of improved contact between vocal cords and better vibratory characteristic. Divakaran et al [2] in 2016 analysed outcome analysis of Co2 laser and found mean shimmer 4.6 and 5 in males and females respectively which is above the threshold for PRAAT software by Teixeira et al [12]. In our study this value is less than 3.81 in both genders which is considered as better improvement.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…The improvement in the acoustic parameters can be explained on the basis of improved contact between vocal cords and better vibratory characteristic. Divakaran et al [2] in 2016 analysed outcome analysis of Co2 laser and found mean shimmer 4.6 and 5 in males and females respectively which is above the threshold for PRAAT software by Teixeira et al [12]. In our study this value is less than 3.81 in both genders which is considered as better improvement.…”
Section: Discussionsupporting
confidence: 39%
“…Various surgical techniques have been established in the management of these lesions i.e., cold knife surgery, laser that can be carbon dioxide laser [2] or diode laser [3] etc. But in a developing country with limited facilities, laryngeal surgeries with cold knife is an affordable measure, with an easy learning curve, less operative time and without having any deterioration in the quality of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They followed up the patients at 2, 6 weeks and 3 months after surgery. There was a significant improvement in the GRBAS scale, they found that preoperative median of GRBAS score was 9, which improved to 6 after 2 weeks and reached score of 2 after 3 months of surgery 14 . In this study, there is a statistically significant difference between both groups regarding the operative time and bleeding in favor of laser technique.…”
Section: Resultsmentioning
confidence: 94%
“…Motta et al mentioned that the value of the CO 2 laser comes from giving better operative hemostasis and no direct tissue contact of the instrument is necessary for resection, improving the view of the operative field giving better working conditions for the surgeon 15 .There are many factors that detect the thermal effects of the laser on tissue, one of them is the physical energy of the chosen laser beam, also water content and tissue vascularity. In general, the use of laser with 5-10 W of power, pulse duration of 0.01"0.05 seconds and a micro spot of 250 mm at 400mm 22 focal length is preferred to minimize thermal side effects 14 . However, the definite adjustment of laser should be selected according to the practical needs of the surgeon, e.g., higher energy and shorter focus for cutting and lower energy and longer focus for coagulation 16 .…”
Section: Resultsmentioning
confidence: 99%
“…The improvement the quality of voice is of fundamental importance, especially in females this type of surgery could be described as “esthetic”. There are several types of surgical approaches described in the literature: classical (or cold steel surgery) [12] when the hyperplasic mucosa of the medial wall is excised with micro instruments, when the mucosa of the medial margin is preserved while aspirating the content of the edema as described by Hirano and confirmed with phonatory parameters analysis [12] , when the sub epithelial layer is coagulated with the laser CO2 [13 , 14] , KTP laser [15 , 16] micro flap [17] or micro suture techniques [18 , 19] .…”
Section: Introductionmentioning
confidence: 99%